Mass spectrometry of intact V-type ATPases reveals bound lipids and the effects of nucleotide binding. - Zhou, M; Morgner, N; Politis, A; Isaacson, S; Matak-Vinković, D; Murata, T; Bernal, R; Stock, D; Robinson, C (2011)
The ability of electrospray to propel large viruses into a mass spectrometer is established and is rationalized by analogy to the atmospheric transmission of the common cold. Much less clear is the fate of membrane-embedded molecular machines in the gas phase. Here we show that rotary adenosine triphosphatases (ATPases)/synthases from Thermus thermophilus and Enterococcus hirae can be maintained intact with membrane and soluble subunit interactions preserved in vacuum. Mass spectra reveal subunit stoichiometries and the identity of tightly bound lipids within the membrane rotors. Moreover, subcomplexes formed in solution and gas phases reveal the regulatory effects of nucleotide binding on both ATP hydrolysis and proton translocation. Consequently, we can link specific lipid and nucleotide binding with distinct regulatory roles.